Measurements of heat loss and its distribution for the COREX-3000 ironmaking process. Issue 2 (23rd April 2014) - Shen, W.; Wu, S.-L.; Du, K.-P.; Kou, M.-Y.; Sun, Y.
Abstract : The accuracy of the parameters is of great importance in the calculation and simulation of the COREX process. Therefore, it is necessary to measure some parameters, especially the heat loss and its distribution, which have not been reported before. Based on the characteristics of the two sets of the Baosteel COREX-3000 process, a method and standard are established for the heat loss and its distribution. Then the heat loss and distribution are calculated based on the measured parameters. The results show that the total heat loss of the two COREX processes is 495.4 MJ/tHM and 413.7 MJ/tHM. The heat loss caused by cooling water accounts for more than 93% of the total heat loss while the heat loss of furnace shells is less than 7%. The main heat loss caused by cooling water takes place at the tap hole zone, which is also the part of the COREX system with the most heat loss Its heat loss is about 30% of the heat loss caused by cooling water and 28% of the total heat loss of the COREX system. The main heat loss of furnace shells takes place at the dome of the melter-gasifier and the reducing gas entrance position of the shaft furnace, where the heat loss accounts for nearly 90% of the heat loss of furnace shells. It is also found that the energy utilization efficiency of the 1# COREX system is much lower than that of the 2# COREX system after comparison.